Suitability of screened fungi for solid state fermentation (1999)
Seven fungi were screened to determine their suitability for solid-state fermentation. In a 5-day submerged fermentation Aspergillus niger, Aspergillus oryzae, Fusarium oxysporum, Rhizopus isolate, Amtillaria mellea and Rhizopus sexualis recorded 166.49, 122.60, 50.58, 23.94. 17.94 and 39.80 mg/ 100 ml biomass production respectively. Pleurotus ostreatus did not show any growth. However the colony radial growth rates of A. niger, A. oryzae, F. oxysporum and P. ostreatus varied from 10.50-76.88 mm over a 7-day growth period. The best colony radial growth rate of 76.88 mm was obtained for A. niger while 49.83, 73.83 and 50.50 mm were obtained for A. oryzae, P. ostreatus and F. oxysporum respectively. A positive correlation was obtained between colony radial growth rates and rate of starch utilization by the fungi. The overall result indicated that A. niger and A. oryzae had superiority over other fungi for all the parameters studied. They are therefore recommended for future studies of protein enrichment of starchy Substrates by solid state fermentation.